(untitled) (Palimpsesto, 2023)
From a critical perspective of the autonomy of art, in this paper we will outline the main aesthetic categories of pre-Hispanic Andean philosophy. We will base our study on anthropological studies, but we will also contrast, our object of study with the Western aesthetics of reception represented in our scheme by Jauss in his Small Apology for The Aesthetic Experience (1972). In this double procedure, we will focus on the figure of the textile for its condition of being a central cultural product of the people in the Andes. We will see, that the textile condenses several categories of the andean aesthetics. Once we establish this aproach, we will proceed to highlight the features of the Andean aesthetic that we find in the novel Cuando Sara Chura despierte (2003) by the Bolivian Juan Pablo Piñeiro. Here we will defend that the narrative construction of Piñeiro has a simile with the construction of a textile. We are interested in highlighting how in the literary production to which we refer, both the pre-Hispanic Andean aesthetic and the figure of the textile catalyze sensitive possibilities in their reception, operating in them a decolonial social criticism, which must be rescued.